METAL LINE DETECTION: A NEW SENSORY SYSTEM FOR LINE FOLLOWING MOBILE ROBOT - Ab Rashid, Mohd Zamzuri; Shah, HNM; Mohd Aras, Mohd Shahrieel; Kamarudin, Muhammad Nizam; Mohammed Kassim, Anuar; Jaafar, Hazriq Izzuan (Little Lion Scientific Islamabad Pakistan, 2014)
This paper presents a new type of line following robot that uses metal sensor to detect metal line and maneuver around based on that line. The paper focused on developing the hardware model of automated guide vehicle (AGV) system and integrating it with metal detection sensor. The system performance is measured in a straight line movement and when the robot turns at specific degrees.The metal line following robot can be used to move objects in daily life operation, warehouse operations or manufacturing facility to any desired location automatically. A metal line with certain length can be placed on the desired floor to indicate the path that the robot requires to move. Based on the experimental studies, it showed that the mobile robot can maneuver and track the metal line that is attached on the floor by utilizing three inductive proximity sensor located in front of the robot. This sensory system can be used as alternative sensor instead of using line following sensor which normally based on the infrared proximity detector. The line following robot that operates based on the metal line capable to overcome the problem of different light intensity reflection.